2016
DOI: 10.1182/blood-2015-10-675140
|View full text |Cite
|
Sign up to set email alerts
|

Men with severe hemophilia in the United States: birth cohort analysis of a large national database

Abstract: Key Points Prospectively collected data on demographics, complications, and mortality are described for 4899 US men with severe hemophilia. Analyzing multiple birth cohorts of US men with severe and mild hemophilia demonstrates ongoing morbidity in need of surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
133
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(139 citation statements)
references
References 30 publications
3
133
1
2
Order By: Relevance
“…33 The long-term outcomes regarding sustained, stable factor IX coagulant activity on joint health and quality of life are not yet known. Recent preclinical work has shown that factor IX products with an extended half-life improved synovial and osteochondral healing after hemarthrosis in mice with hemophilia B, whereas short-term factor IX replacement for hemostasis did not prevent arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…33 The long-term outcomes regarding sustained, stable factor IX coagulant activity on joint health and quality of life are not yet known. Recent preclinical work has shown that factor IX products with an extended half-life improved synovial and osteochondral healing after hemarthrosis in mice with hemophilia B, whereas short-term factor IX replacement for hemostasis did not prevent arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In this context, more and more of them are becoming confronted with a new challenge: ageing. Ageing influences their well-being, because older PWH carry the burden of the physical and psychological consequences of the inadequate treatment received in the early periods of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…4,16 Presence of target joints has been associated with fatigue, loss of enjoyment, reduced leisure pursuits and particularly pain, with more than eight times as many patients reporting extreme pain or discomfort in the presence of a target joint. 4,16 Presence of target joints has been associated with fatigue, loss of enjoyment, reduced leisure pursuits and particularly pain, with more than eight times as many patients reporting extreme pain or discomfort in the presence of a target joint.…”
Section: Milestone 2 Minimal Joint Impairment/ Improved Quality Ofmentioning
confidence: 99%